Applications of End-Tidal Carbon Dioxide (ETCO2) Monitoring in Emergency Department; a Narrative Review - Aminiahidashti, Hamed; Shafiee, Sajad; Zamani Kiasari, Alieh; Sazgar, Mohammad (Archives of Academic Emergency Medicine, 2018)
Capnograph is an indispensable tool for monitoring metabolic and respiratory function. In this study, the aim was to review the applications of end-tidal carbon dioxide (ETCO2) monitoring in emergency department, multiple databases were comprehensively searched with combination of following keywords: â€œETCO2â€, â€œemergency department monitoringâ€, and â€œcritical monitoringâ€ in PubMed, Google Scholar, Scopus, Index Copernicus, EBSCO and Cochrane Database.